An Audiences’ Perception of Ghanaian Television Drama Series on National Values - Aketema, Joseph; Nana Beyin Kwaku Ofori, Emmanuel; Tetteyfio Manu, Sylvia (The Journal of Society and Media, 2024)
This paper examines students’ views regarding television series in line with the cultural and ideological broadcasting of Ghana’s regulations. With the main objective of evaluating the effects and influences of Ghana’s television series on audiences lived experiences, both qualitative and quantitative methodological approaches were used to evaluate a purposively sampled University of Ghana’s student body on their perception of Ghana’s television content. Key findings indicates that there is an -increasing enculturation of Ghanaian culture by Euro-American media products. This has proven to have serious effects on the local content producers and consumers alike. The study recommends an enforcement of regulatory body of foreign content while encouraging indigenous content production and exhibition.